(untitled) (Fiep Bulletin - online, 2012)
The object of the present study was to verify the reasons to adherence and also the impacts of the working out in a medium-sized gym, placed in Rio de Janeiro downtown. It is a quantitative research and its better known model is the survey of opinions (BAUER et. al., 2003), so it was used a descriptive statistics in order to analyze and to discuss the data. Sixty two people, equally divided by sex, took place in the research. The results show that the average age is 31,54 ± 10,27 years, the amount of times spend practicing gym (2,7 years), working out (4,2 years), in which training session (71,45 min) and the time per week (4,1). The manly reasons to working out was the health (47) and the esthetics (41), 48% of them are hypertrophied because of the kind of series, 23% wait only one minute before change the series and 37% practice aerobic exercises. Heredity showed hypertension in 30%, allergy (12%) as a disease reported and injuries to health with 13% change in mood. Upon the facts stated a large portion of the attendees of the gym started to work out with the goal of health associated with aesthetics, once that the preferred training prescription was anchored in muscle hypertrophy.